2014
DOI: 10.1016/j.jvb.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive predictors of well-being in African college students

Abstract: A four-year qualitative study of working-class students, conducted at a large research university in Canada, found that these students had transformed their habitus through immersion in the social life of the university. They moved away from their old selves, families, and peers. The students reported drifting away from their old friends as a part of growing older and also as a result of growing intellectually. Although the students transformed their habitus, they still experienced uncertainty between their ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 26 publications
5
39
0
3
Order By: Relevance
“…According to Lent et al (1994) , self-efficacy is the key structure of SCCT and is believed to have a direct impact on behavior. This implies that SSE can be seen as an important cognitive variable in the process of interpreting an individual’s formative behaviors, alongside interaction with the environment ( Lent et al, 2014 ; Sheu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Lent et al (1994) , self-efficacy is the key structure of SCCT and is believed to have a direct impact on behavior. This implies that SSE can be seen as an important cognitive variable in the process of interpreting an individual’s formative behaviors, alongside interaction with the environment ( Lent et al, 2014 ; Sheu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive emotions that students experience in academic settings (e.g., enjoyment, hope, enthusiasm, vigor) are found to be positively related to their learning motivation (Mega, Ronconi, & De Beni, ; Patrick, Hisley, & Kempler, ). Similarly, several researchers (Lent et al, ; Ojeda, Flores, & Navarro, ) have found that when students experience high levels of positive emotion, they are more likely to feel satisfied with their academic experience. In contrast, negative academic emotions (e.g., boredom, anxiety, anger) appear to be detrimental to students’ learning motivation (Pekrun, Goetz, Frenzel, Barchfeld, & Perry, ; Tze, Daniels, & Klassen, ).…”
Section: The Impact Of Students’ Emotions On Students’ Academic Expermentioning
confidence: 84%
“…Only by establishing and maintaining network relationships can they achieve their goals. Knowledge and resources are needed (Lent et al, 2014;Sheu et al, 2014). Furthermore, teamwork can also be seen as a strong network relationship, and the process of students solving problems and achieving tasks through teamwork will positively affect their employability.…”
Section: Student Employability and Self-efficacymentioning
confidence: 99%
“…Social cognition scholars argue that individuals’ behavioral outcomes will be influenced by both environmental and cognitive factors in a given situation, especially those beliefs that lead to success and behavior ( Lent et al, 2014 ; Wang et al, 2016 ). They call these beliefs “self-efficacy,” an important cognitive variable in personal factors during the process of interpreting individual formative behaviors, and interaction with the environment ( Lent et al, 2014 ; Sheu et al, 2014 ). It can also be seen as the basis for human behavioral motivation, mental health and personal achievement ( Dacre and Qualter, 2013 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%